1998
DOI: 10.1038/sj.bjp.0701823
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and cardiovascular effects of the μ‐opioid receptor agonist [Lys7]dermorphin in awake rats

Abstract: 1 Changes in respiratory variables, arterial blood pressure and heart rate were studied in awake rats after injection of the opioid peptide [Lys 7 ]dermorphin and its main metabolites, [1][2][3][4][5]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The MAP-lowering activity of loperamide likely occurs through the activation of opioid receptors in peripheral tissues because loperamide does not cross the blood-brain barrier [9] . Furthermore, 1 -opioid receptors probably play only a minor role in this process because loperamide's effects were minimally affected by naloxonazine pretreatment; this view is consistent with a previous report [25] .…”
Section: Discussionsupporting
confidence: 81%
“…The MAP-lowering activity of loperamide likely occurs through the activation of opioid receptors in peripheral tissues because loperamide does not cross the blood-brain barrier [9] . Furthermore, 1 -opioid receptors probably play only a minor role in this process because loperamide's effects were minimally affected by naloxonazine pretreatment; this view is consistent with a previous report [25] .…”
Section: Discussionsupporting
confidence: 81%
“…In these studies, the increased tidal volume was unable to fully compensate for the frequency decrease, and thus minute volume was generally depressed after opioid treatment, as reported for most opioid studies on respiration (Isom et al, 1969;van den Hoogen and Colpaert, 1986). Several other studies have, however, observed either no effect or an increase in minute volume with the administration of various doses of opioid agonists, emphasising that some respiratory effects of opioids remain unresolved (Czapla et al, 2000;Kokka et al, 1965;Negri et al, 1998). These effects, however, may be methadone specific due to its ability to act on both opioid and non-opioid (NMDA receptor) sites (Gorman et al, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…This increase of ventilation, after inhibiting central opioid receptors, observed at 2, 5, and 10 minutes of hypoxia seems to be attenuated by decreased breathing frequency at 20 minutes of hypoxia. A recent study shows that analgesic doses of [Lys7] dermorphin stimulate respiration (as opposed to ventilatory depression) by activating central μ opioid receptors, and this respiratory stimulation involves activation of a forebrain serotoninergic excitatory pathway during both room air and hypoxic exposures (27). This important observation indicates that different brain locations, neurointeractions, and different types of opioid receptors may result in different effects on respiratory neuron and respiratory effector responses.…”
Section: Discussionmentioning
confidence: 99%